THE IMPACT OF DIGITALIZATION AND GLOBALIZATION ON THE DEVELOPMENT OF WORLD AND RUSSIAN FASHION MARKET - Ekaterina V. Malysheva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article tries to formulate and show the principle trends of global economy, such as globalization and informatization, which impact the  world fashion market. It summarizes the world experience of state  support of enterprises’ export activities abroad and analyzes current  state measures of support to export of Russian enterprises and the  efficiency of promoting the brand ‘Made in Russia’ and the program of  production localization in Russia. The author discusses the problems of  controversial customer demand – escapism and hedonism and shows  ways of their solving through differentiation of company activity in fashion industry aimed at target audience extension.